2020
DOI: 10.1029/2019gl084787
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Energy Budget of Laboratory Fault Slip Using Rotary Shear Experiments and Micro‐Computed Tomography

Abstract: Quantitative assessment of the energy budget of earthquake events is one of the key aspects for understanding the physics of earthquakes. Investigation of laboratory fault slips under controlled conditions can provide insights on this important aspect of the natural and induced earthquakes. We conducted a rotary shear experiment under X‐ray micro‐computed tomography, which allowed in situ and operando measurement of macroscopic stresses and imaging of the newly formed fractures inside the sample. We estimate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This strain energy was consumed in the formation of off-fault damage, and the energy dissipated in frictional slip decreased relative to the smooth fault experiment. A low amount of energy dissipated by off-fault damage was also identified in a series of in situ rotary shear X-ray microtomography experiments performed on cement mortar (Zhao et al, 2020). This study imaged the development of off-fault damage and found that the fracture energy produced by this damage was less than 0.3% of the total energy budget, in agreement with experiments where a fault propagated subcritically and created damage at its tip (Aben et al, 2019).…”
Section: Damage Development and Secondary Faultingsupporting
confidence: 75%
“…This strain energy was consumed in the formation of off-fault damage, and the energy dissipated in frictional slip decreased relative to the smooth fault experiment. A low amount of energy dissipated by off-fault damage was also identified in a series of in situ rotary shear X-ray microtomography experiments performed on cement mortar (Zhao et al, 2020). This study imaged the development of off-fault damage and found that the fracture energy produced by this damage was less than 0.3% of the total energy budget, in agreement with experiments where a fault propagated subcritically and created damage at its tip (Aben et al, 2019).…”
Section: Damage Development and Secondary Faultingsupporting
confidence: 75%
“…We chose this segmentation workflow, rather than more elaborate procedures, such as Hessian filter (Voorn et al, 2013) or machine learning (e.g., Andrew, 2018; Zhao et al, 2020), because it is well established and contains only one parameter (the grayscale threshold). Several studies have estimated the effect of using different segmentation techniques on the variability of the segmented porosity or fracture surface area (e.g., Voorn et al, 2013; Zhao et al, 2020) and found that these techniques could estimate that the difference in the segmented fracture surface area between different techniques could be up to 20% (e.g., Figure 4 in Zhao et al, 2020). In most studies, the segmented fracture surface area or porosity cannot be compared with a ground‐truth value, so it is not possible to provide an actual error of the porosity for a given segmentation procedure, but only a variability of possible values.…”
Section: Methodsmentioning
confidence: 99%
“…Journal of Geophysical Research: Solid Earth Zhao et al, 2020). In most studies, the segmented fracture surface area or porosity cannot be compared with a ground-truth value, so it is not possible to provide an actual error of the porosity for a given segmentation procedure, but only a variability of possible values.…”
Section: 1029/2020jb020354mentioning
confidence: 99%
“…The dynamics of earthquakes are primarily controlled by the balance between the available elastic strain energy (in the surrounding medium), the energy consumption for advancing the rupture front, the necessary work against the frictional resistance, and the release of seismic energy (waves) from the source (Cooke & Murphy, 2004). A large body of research has been carried out to constrain the energy budget of earthquakes (Chester et al., 2005; Cooke & Murphy, 2004; McGarr, 1999; Nielsen, Spagnuolo, Smith, et al., 2016; H. Noda et al., 2013; Ohnaka, 2003; Okubo et al., 2019; Passelègue et al., 2016; Zhao et al., 2020). Most of them focus on breakdown energy, because it can better represent fault properties compared with specific aspects of the weakening process (Nielsen, Spagnuolo, Smith, et al., 2016).…”
Section: Introductionmentioning
confidence: 99%